Comparison of the diagnostic value of the visual inspection with acetic acid (VIA) and Pap smear in cervical cancer screening - Zahra Vahedpoor; Mitra Behrashi; Tahereh Khamehchian; Masoumeh Abedzadeh-Kalahroudi; Alireza Moravveji; Mona Mohmadi-Kartalayi (Elsevier, 2019)
Objective: This study aimed to compare the diagnostic value of VIA with Pap smear in screening for cervical cancer. Materials and methods: In this cross-sectional study, 440 women who had eligibility criteria, in Kashan city were assessed. All women underwent Pap smear test and then a visual inspection with acetic acid and colposcopy-biopsy (Gold Standard). Then, the diagnostic value indices including the specificity, sensitivity, positive and negative predictive values for the results of VIA and Pap smear were analyzed by SPSS V16 software. Results: Finding showed that 29.9% of women had abnormal Pap smear. The false positive rate of Pap smear was 40.2%, and its false negative rate was 37.4%. For VIA, the false positive and false negative rates were 21.2% and 4.6%. The sensitivity, specificity, NPV and PPV of Pap smear was 29.7%, 85.5%, 59.8%, 62.6%, and these values for VIA was 94.6%, 81.6%, 78.8%, 95.4% respectively. Combination of Pap smear and VIA showed the sensitivity of 97.3% and 100% in low grade and high grade cervical lesions. Conclusion: VIA has a higher sensitivity than Pap smear in detection of low and high grade cervical lesions, however, its specificity is less than Pap smears. Therefore it is recommended to use of VIA along with Pap smear to reach a higher sensitivity. Keywords: Cervical cancer, Pap smear, VIA, Screening, Colposcopy